Pedestrian Area Development in Smart City Concept in Tangerang City - Ali Haj Fathur; Adie Dwiyanto Nurlukman; Yusuf Fadli (Trunojoyo University of Madura, 2022)
The city government of Tangerang has not been able to apply the concept of smart cities, while urban development has not used the concept of smart (intelligen) and attractive (attractive) which facilitates infrastructure, technology, and attracts local people based on a forward vision regarding the needs, capabilities and resources that exist. , safe and comfortable pedestrian facilities, and public spaces for pedestrians that can create an urban cultural concept that can provide business controversies that can help migrants and communities enjoy the city by foot. The purpose of this study is to study how the Tangerang City government can implement a development system that can be lived in and can be visited in accordance with the Tangerang Direct motto. This study uses a qualitative method that studies the literature with systematic literature review techniques by descriptive data analysis. The results of this study indicate that the Tangerang city government has just realized the construction of a pedestrian lane with a ratio of 72.40% of the length of the city road which has a length of 316.46 km with a very narrow space dimension of 1.5 meters combined with greening areas.